Role of the prostaglandin E2 EP1 receptor in traumatic brain injury. - Alexander V Glushakov; Jawad A Fazal; Shuh Narumiya; Sylvain Doré (PLoS ONE)
Brain injuries promote upregulation of so-called proinflammatory prostaglandins, notably prostaglandin E2 (PGE2), leading to overactivation of a class of its cognate G-protein-coupled receptors, including EP1, which is considered a promising target for treatment of ischemic stroke. However, the role of the EP1 receptor is complex and depends on the type of brain injury. This study is focused on the investigation of the role of the EP1 receptor in a controlled cortical impact (CCI) model, a preclinical model of traumatic brain injury (TBI). The therapeutic effects of post-treatments with a widely studied EP1 receptor antagonist, SC-51089, were examined in wildtype and EP1 receptor knockout C57BL/6 mice. Neurological deficit scores (NDS) were assessed 24 and 48 h following CCI or sham surgery, and brain immunohistochemical pathology was assessed 48 h after surgery. In wildtype mice, CCI resulted in an obvious cortical lesion and localized hippocampal edema with an associated significant increase in NDS compared to sham-operated animals. Post-treatments with the selective EP1 receptor antagonist SC-51089 or genetic knockout of EP1 receptor had no significant effects on cortical lesions and hippocampal swelling or on the NDS 24 and 48 h after CCI. Immunohistochemistry studies revealed CCI-induced gliosis and microglial activation in selected ipsilateral brain regions that were not affected by SC-51089 or in the EP1 receptor-deleted mice. This study provides further clarification on the respective contribution of the EP1 receptor in TBI and suggests that, under this experimental paradigm, the EP1 receptor would have limited effects in modulating acute neurological and anatomical pathologies following contusive brain trauma. Findings from this protocol, in combination with previous studies demonstrating differential roles of EP1 receptor in ischemic, neurotoxic, and hemorrhagic conditions, provide scientific background and further clarification of potential therapeutic application of prospective prostaglandin G-protein-coupled receptor drugs in the clinic for treatment of TBI and other acute brain injuries.